Análisis cariotípico de Famatina andina (Phil.) Ravenna (Amaryllidaceae): primer registro de una Hippeastreae sudameri cana con constricciones secundarias centroméricas - Baeza, Carlos; Macaya, Jorge (Gayana Botánica, 2020)
Bulbs were collected from a population of Famatina andina (Phil.) Ravenna in central Chile. Their chromosomes were analyzed and it was observed that the cariotypic formula and chromosomal number are identical to Famatina cisandina Ravenna. Secondary centromeric constrictions were also observed in chromosomes 1, 2 and 7, and the nucleolus organizing region (NOR) was not observed in the long arm of chromosome 7. This is the first report of secondary centromeric constrictions in South American Hippeastreae.